Concepções sobre o câncer e o seu tratamento no contexto hospitalar e escolar - Reis, Solange Kapp da Costa dos (2010)
In this study was analysed the conceptions about cancer and its treatment on the educational context under two aspects: in the hospital and at school, though active intervention of the pharmaceutical professional. In the hospital ambient was elected the pharmacy service of Santa Maria university hospital, in the chemotherapy department. The patients who were chosen were using the medicine imatinib mesylate, indicated to chronic myeloid leukemia (CML). In relation to the patients, was applied an initial questionnaire with the purpose to know what do they know about their disease, the treatment and the medicine action, with later return according with their doubts and difficulties, by means of resources like folders and others explanatory materials. At schools the primary goals was aimed to know what the students know about cancer and alert about the ways and the importance of prevention and the treatment. In this case, questionnaires were used as resources, before and after of the explanatory class. The students demonstrated some difficulty to answer what is cancer , where it occurs or how can be prevented. Regarding the patients, was found that most of them show difficulties to understand about their disease, their treatment or the medicine action. It can be concluded that the work demonstrated to be useful, both in the school as in the hospital due to coverage that the cancer reaches in the news and it would be very important to continue to this work, focusing mainly in the educative actions and prevention, in both environments.